A Taxonomy of Fabric Integrated Thermal Energy Storage: A review of storage types and building locations. Issue 1 (26th January 2018) - Marinho de Castro, Maria Manuela; Sharpe, Tim; Kelly, Nicolas; Allison, John
Thermal energy storage incorporated into the fabric of buildings could provide the opportunity to significantly improve the use of energy from renewable sources and take maximum advantage of off-peak electricity tariffs. If this kind of thermal storage is integrated into the structure of the building itself, the internal space of the building is not compromised and may be more cost-effective. In this paper, the authors present a taxonomy of currently available fabric-integrated thermal energy storage solutions based on a review of existing literature. The aim of this study is to map the range of extant design solutions for fabric-integrated thermal storage in buildings and detect any omissions. The taxonomy presented in this paper takes into consideration the interaction between the storage of thermal energy and the thermal zones of buildings, the methods and medium used to store thermal energy, and the storage temperature. Also considered here are the different architectural integration options, which the authors present through a catalogue of possible thermal energy storage locations. This paper also argues that an active storage system provides a means for energy systems in buildings to actively participate in future energy networks, which may require active load management to accommodate a high proportion of renewable technologies. Active storage allows the charge and discharge of the thermal energy stored within buildings when the energy is available and/or economically valuable. This kind of active participation is not possible with passive storage techniques.